Cuticular hydrocarbon analysis in forensic entomology. (16th May 2019) - Moore, Hannah
Abstract : Blowflies are the first inhabitants of decomposing remains and are therefore of forensic relevance for post mortem interval estimations. Forensic entomology is becoming widely accepted as a branch of forensic science and is being utilised more within forensic casework. This wider use has driven an increase in research being carried out within the field, in particular, in less "classical" techniques such as DNA and chemical analysis in the form of cuticular hydrocarbon analysis. This short review will examine the research currently being studied in the area of cuticular hydrocarbon analysis of forensically important Diptera for species identification and ageing.